2009
DOI: 10.1002/hipo.20560
|View full text |Cite
|
Sign up to set email alerts
|

Age effects on the regulation of adult hippocampal neurogenesis by physical activity and environmental enrichment in the APP23 mouse model of Alzheimer disease

Abstract: An active lifestyle is to some degree protective against Alzheimer's disease (AD), but the biological basis for this benefit is still far from clear. We hypothesize that physical and cognitive activity increase a reserve for plasticity by increasing adult neurogenesis in the hippocampal dentate gyrus (DG). We thus assessed how age affects the response to activity in the murine APP23 model of AD compared with wild type (WT) controls and studied the effects of physical exercise (RUN) and environmental enrichment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
119
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(130 citation statements)
references
References 51 publications
6
119
1
4
Order By: Relevance
“…Although the concept of a reduction in hippocampal neurogenesis preceding the development of A␤ plaques may account for the onset of cognitive decline, further studies are required to pinpoint exactly where alterations in hippocampal neurogenesis occur in relation to other pathologies in the development of AD. There have also been reports of increased hippocampal neurogenesis in mouse models of AD (Ermini et al, 2008;Jin et al, 2004a;Mirochnic et al, 2009;Verdaguer et al, 2015;Yu et al, 2009). It is likely that differences in animal models, the age at which they are studied, extent of A␤ pathology and method of assessment of neurogenesis, in particular BrdU administration protocols, all affect comparisons across these studies and may account for some of the differences observed with some studies reporting reductions in neurogenesis and others reporting increases.…”
Section: Alterations In Hippocampal Neurogenesis In Ad Mouse Modelsmentioning
confidence: 99%
“…Although the concept of a reduction in hippocampal neurogenesis preceding the development of A␤ plaques may account for the onset of cognitive decline, further studies are required to pinpoint exactly where alterations in hippocampal neurogenesis occur in relation to other pathologies in the development of AD. There have also been reports of increased hippocampal neurogenesis in mouse models of AD (Ermini et al, 2008;Jin et al, 2004a;Mirochnic et al, 2009;Verdaguer et al, 2015;Yu et al, 2009). It is likely that differences in animal models, the age at which they are studied, extent of A␤ pathology and method of assessment of neurogenesis, in particular BrdU administration protocols, all affect comparisons across these studies and may account for some of the differences observed with some studies reporting reductions in neurogenesis and others reporting increases.…”
Section: Alterations In Hippocampal Neurogenesis In Ad Mouse Modelsmentioning
confidence: 99%
“…189 A reduction in brain b-amyloid deposition after EE exposure has also been shown in APP, TgCRND8 and AD11 transgenic mice. 186,187,190,191 Some studies have also investigated the effects of EE on neurogenesis in AD mouse models. Although conditional PS1 knockout mice and mice overexpressing either wild-type human PS1 or the mutant form P117L show a deficiency in EE-induced neurogenesis, [192][193][194] it has been recently reported that EE promotes hippocampal neurogenesis in APP and TgCRND8 mice.…”
Section: Impact Of Ee On the Brain L Baroncelli Et Almentioning
confidence: 99%
“…Although conditional PS1 knockout mice and mice overexpressing either wild-type human PS1 or the mutant form P117L show a deficiency in EE-induced neurogenesis, [192][193][194] it has been recently reported that EE promotes hippocampal neurogenesis in APP and TgCRND8 mice. 185,191,195 Moreover, EE increases angiogenesis and facilitates blood Ab clearance through a differential regulation of Ab receptor/transporter molecules in TgCRND8 mice. 196 Lazarov et al 189 carried out a microarray analysis to identify gene expression changes in APP/PS1 transgenic mice placed in EE conditions.…”
Section: Impact Of Ee On the Brain L Baroncelli Et Almentioning
confidence: 99%
“…Rodents with anhedonia, as can be induced by long-term impoverished caging [26] and also varies with strain [27] with enrichments that to other rodents act as valued incentives. Overall, variation between rodents in neophobia and anhedonia may thus help explain why not just strain, but also sex, age and individual characteristics can influence experimental outcomes, even when enrichments are carefully standardized [28][29][30][31][32][33][34][35]. Here, we therefore used individual variation in responses to standardized enrichments to conduct preliminary tests of the hypotheses that neophobia and anhedonia affect the extent to which mice interact with environmental enrichments.…”
Section: Introductionmentioning
confidence: 99%